Multilayer nanostructure metal hydride and preparation method thereof
By forming a nanometal catalyst on the carbon material support and supporting coordination hydrides on its surface to form multi-layer nanostructured metal hydrides, the problems of high hydrogen absorption and discharge temperature, slow kinetics and poor reversibility of LiBH4 are solved, and high hydrogen storage density and improved kinetic performance are achieved.
Patent Information
- Application Number
- CN202411509699.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing hydrogen storage technology cannot take into account safety, hydrogen storage capacity and cost, especially for the high hydrogen absorption and discharge temperature, slow kinetics and poor reversibility of LiBH4.
A nanometal catalyst is formed by performing a hydrogen thermal reduction reaction on the carbon material support, and then a coordination hydride is supported on the surface of the transition metal and/or the carbon material by solvothermal reaction to form a multi-layer nanostructured metal hydride.
The preparation of multi-layer nanostructured metal hydrides has high hydrogen storage density and improved hydrogen absorption and release kinetics, which reduces the hydrogen absorption temperature and improves reversibility.
Smart Images

Figure CN119528087A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage materials and nano materials, and in particular relates to a multilayer nanostructured metal hydride and a preparation method thereof. Background Art
[0002] Energy is the basis for supporting individual and social activities. The excessive consumption of traditional fossil fuels has not only caused an energy crisis, but also brought about a series of environmental pollution and health problems. Hydrogen energy, as a new type of renewable energy with abundant reserves, high energy density, and clean and pollution-free, is considered to be an ideal energy alternative in the future. However, as an energy carrier, hydrogen is in a gaseous state at room temperature and atmospheric pressure, resulting in its extremely low volume energy density, which leads to huge challenges in its practical application in terms of production, storage and utilization. In particular, safe, efficient and economical hydrogen storage technology has always been a key bottleneck restricting the practical application and scale of hydrogen energy.
[0003] Although the technology of high-pressure gaseous hydrogen storage (room temperature, 350-700 bar) and low-temperature liquefied hydrogen storage (-253°C, 5-10 bar) is relatively mature, it cannot take into account safety, hydrogen storage capacity and cost. Metal hydrides in chemical hydrogen storage materials store hydrogen by forming chemical bonds between hydrogen atoms and materials. They have good safety and high hydrogen storage capacity and have great application development prospects, including simple metal hydrides (MgH2) and coordinated hydrides (LiBH4, NaAlH4).
[0004] As a typical coordination hydride, lithium borohydride (LiBH4) has high mass hydrogen storage density (18.5wt%) and volume hydrogen storage density (121kg / m 3), which has attracted extensive attention from researchers. However, the process of LiBH4 hydrogen absorption and desorption involves the breaking and recombination of multiple chemical bonds. The high thermodynamic stability and reaction energy barrier make its operating temperature high, the kinetics slow and the reversibility poor, which is not conducive to the application of vehicle-mounted hydrogen storage. Therefore, reducing the hydrogen absorption and desorption temperature of LiBH4 and improving reversibility have always been the focus of research in this field. At present, the modification research on LiBH4 hydrogen storage materials mainly focuses on the four aspects of reactant destabilization, anion and cation substitution, catalytic doping and nano-sizing. Catalyst doping is the most studied modification method at present, which can significantly improve the hydrogen absorption and desorption kinetics of LiBH4. Based on the catalytic modification method, researchers have successively found that Ti-, Zr-, Nb-, Ni- and Co-based catalysts have a significant improvement on the de / hydrogenation kinetics of LiBH4. Compared with transition metal oxide and halide catalysts, which easily react with LiBH4 to produce by-product LiCl during heating, the introduction of metal catalysts is more suitable for the system. In 2009, Yu et al. found that the addition of metal Ni to LiBH4 not only improved the hydrogen desorption kinetics, but also greatly reduced the hydrogen absorption temperature. Therefore, metal-based catalysts have a highly efficient catalytic effect on the absorption and desorption of hydrogen by LiBH4. However, the thermodynamics of LiBH4 is relatively stable, and the improvement of the cyclic stability of LiBH4 by the catalyst is very limited. While nano-sizing can achieve kinetic regulation of LiBH4, it can also change the thermodynamic properties of LiBH4 and improve the reversibility of LiBH4. Unsupported LiBH4 will inevitably melt during the hydrogen desorption process, causing its particles to agglomerate. Therefore, the nano-sizing of LiBH4 currently requires the use of carrier materials to achieve nano-confinement. In order to further improve the comprehensive hydrogen storage performance of LiBH4, it is necessary to fully combine the advantages of catalytic doping and nano-confinement. Therefore, the synergistic modification research of nano-sizing and nano-catalysis is very necessary.
[0005] MgH2 has become one of the high-capacity hydrogen storage materials that may be put into practical use in the near future due to its abundant raw material reserves and high hydrogen storage content (7.6wt%). However, due to its poor thermodynamic properties and slow kinetic performance, the hydrogen absorption and desorption temperature of MgH2 is too high to meet the requirements of practical use. Adding catalysts and nano-sizing are effective means to reduce the kinetic energy barrier of hydrogen absorption and desorption of MgH2. Similarly, the synergistic modification of nano-sizing and nano-catalysis is also effective in improving the hydrogen absorption and desorption performance of MgH2.
[0006] At present, the research on synergistic modification of nano-sizing and catalytic doping cannot simultaneously meet the requirements of high hydrogen storage capacity and suitable operating temperature. Summary of the invention
[0007] The invention provides a method for preparing a multilayer nanostructured metal hydride. The multilayer nanostructured metal hydride prepared by the preparation method has higher hydrogen absorption and storage capabilities.
[0008] The present invention provides a method for preparing a multilayer nanostructured metal hydride, comprising:
[0009] (1) adding a transition metal ion salt and a carbon material to a polar solvent, mixing, heating and stirring to obtain a solid powder, and subjecting the solid powder to a hydrogen thermal reduction reaction to obtain a functionalized carbon material;
[0010] (2) adding a metal hydride raw material and a functionalized carbon material into an organic solvent, ultrasonically treating and mixing to obtain a mixed solution, wherein the metal hydride raw material is a mixture of an alkyl metal Mg compound or an alkyl metal Li compound and a borane compound;
[0011] (3) Under a hydrogen atmosphere, the mixed solution of step (2) is subjected to a solvothermal reaction, and then centrifuged, washed, filtered, and dried to obtain a multilayer nanostructured metal hydride.
[0012] The present invention reduces a transition metal ion salt to a single transition metal loaded on a carbon material carrier through a hydrogen thermal reduction reaction to form a catalyst layer, and then loads a coordinated hydride on the surface of the transition metal and / or the carbon material through a solvent thermal reaction to form a multilayer nanostructure. The transition metal and metal hydride in the multilayer nanostructure are relatively small in size, and the filling rate of the carrier carbon material is high, so that the obtained multilayer nanostructured metal hydride has a relatively high hydrogen storage density.
[0013] Preferably, the mass ratio of the transition metal ion salt to the carbon material is 0.01-100.
[0014] By controlling the content of transition metal ion salt, a single transition metal of smaller size can be dispersed on the carbon material under the synergistic effect of the hydrogen thermal reduction reaction, and the obtained single transition metal and carbon material have good catalytic activity synergistically.
[0015] Further preferably, the mass ratio of the transition metal ion salt to the carbon material is 0.1-10.
[0016] By further controlling the content of transition metal ion salt, a single transition metal with higher density and smaller size can be loaded on the surface of the carbon material, so that the metal hydride can be mostly loaded on a single transition metal active site, thereby forming a multilayer structure.
[0017] Preferably, the transition metal ion salt includes one or more of transition metallocenes, transition metal nitrates, and transition metal chlorides;
[0018] The transition metallocene is one of nickelocene, cobaltocene and titanocene;
[0019] The transition metal nitrate is one of nickel nitrate, cobalt nitrate, iron nitrate, manganese nitrate, chromium nitrate, zinc nitrate, copper nitrate, zirconium nitrate, tungsten nitrate, ruthenium nitrate, rhodium nitrate, hafnium nitrate, palladium nitrate, iridium nitrate, platinum nitrate, scandium nitrate, yttrium nitrate, lanthanum nitrate, cerium nitrate, and praseodymium nitrate;
[0020] The transition metal acetate is one of nickel acetate, cobalt acetate and iron acetate;
[0021] The transition metal chloride is one of titanium tetrachloride, titanium trichloride, zirconium tetrachloride, vanadium trichloride, niobium pentachloride, chromium trichloride, molybdenum pentachloride, manganese dichloride, iron trichloride, iron dichloride, cobalt dichloride, nickel dichloride, copper dichloride, ruthenium trichloride, rhodium trichloride, palladium dichloride, silver chloride, hafnium tetrachloride, tungsten hexachloride, iridium trichloride, platinum tetrachloride, gold trichloride, scandium trichloride, yttrium trichloride, lanthanum trichloride, cerium trichloride, and praseodymium trichloride. The above ionic salts can form transition metal simple substances under appropriate hydrogen thermal reaction.
[0022] Further preferably, the transition metal ion salt is a transition metal nitrate. The decomposition product under the hydrogen thermal reduction reaction is a metal or a gas, which can improve the purity of the product.
[0023] Preferably, the carbon material is one or more of graphene, carbon nanotubes, carbon fibers, porous carbon, carbon nitride, graphene, carbon nanotubes, carbon fibers, porous carbon doped with nitrogen, boron or phosphorus atoms.
[0024] Preferably, the polar solvent is water and / or ethanol. The water and / or ethanol provided by the present invention can dissolve the transition metal ion salt and the carbon material well, and the ratio of water to ethanol only affects the evaporation rate and does not affect the physical and chemical properties of the prepared sample.
[0025] Preferably, the heating and stirring temperature is 60-90°C, the stirring speed is 300-1000rpm, and the stirring time is 3-12h. By controlling the heating and stirring time, the transition metal ion salt can be completely dissolved in the polar solvent. Preferably, the heating and stirring temperature of Ni(NO3)2 in the graphene ethanol solution is 80°C, the stirring speed is 500rpm, and the stirring time is 8h.
[0026] Preferably, in the hydrogen thermal reduction reaction, the gas atmosphere is hydrogen, argon-hydrogen mixture (hydrogen gas volume fraction: 5% to 30%), helium-hydrogen mixer (hydrogen gas volume fraction: 5% to 30%), and nitrogen-hydrogen mixture (hydrogen gas volume fraction: 5% to 30%).
[0027] Preferably, the temperature of the hydrogen thermal reduction reaction is 300°C to 3000°C. As the temperature of the solvent thermal reaction increases, the reaction degree of the raw materials gradually increases, and the yield of the reduced metal also increases accordingly, but too high a temperature will cause the size of the prepared metal element particles to increase and the catalytic activity to decrease. Therefore, metal ions can undergo a reduction reaction at the reaction temperature provided by the present invention. Preferably, the hydrogen thermal reduction reaction temperature of the mixture of Ni(NO3)2 and graphene is 400°C.
[0028] Preferably, the heating time of the hydrogen thermal reduction reaction is 0.5h to 5h. As the solvent thermal reaction time increases, the reaction degree of the raw materials gradually increases, and the output of the reduced metal also increases accordingly, but too long a time will cause the prepared metal element particle size to increase and the catalytic activity to decrease. The specific time needs to be determined by the specific metal salt reducibility and the hydrogen thermal reaction temperature to ensure that the metal ions can be fully reduced and converted into the corresponding metal element within the reaction time. Preferably, the hydrogen thermal reduction reaction time of the mixture of Ni(NO3)2 and graphene at 400°C is 2h.
[0029] Preferably, the alkyl metal Li compound is n-butyl lithium, and the alkyl metal Mg compound is di-n-butyl magnesium and / or bis(cyclopentadienyl) magnesium.
[0030] Preferably, the organic solvent is one or more of n-hexane, cyclohexane, n-heptane, tetrahydrofuran and acetone.
[0031] Further preferably, the alkyl metal Li compound is n-butyl lithium, the molar concentration of the n-butyl lithium in the mixed solution of n-hexane and n-butyl lithium is 0.01-2.0 mmol / ml, and the liquid environment is n-hexane.
[0032] Further preferably, the alkyl metal Li compound is n-butyl lithium, the borane compound is triethylamine borane, and the molar ratio of n-butyl lithium to triethylamine borane is 1:3-1. The amount of triethylamine borane can be the same as or slightly more than that of n-butyl lithium, so that nano lithium hydride can be fully converted into lithium borohydride, and all excess organic matter can be washed away. Preferably, the molar ratio of n-butyl lithium to triethylamine borane is 1:1.3. Selecting this ratio can make nano lithium hydride and triethylamine borane completely react to produce lithium borohydride and avoid waste of raw materials.
[0033] Further preferably, the molar concentration of the alkyl metal Mg compound in the mixed solution of diethyl ether and n-hexane is 0.01-2.0 mmol / ml, and the organic solvent is a mixture of one or more of heptane, n-hexane and diethyl ether. To ensure the yield of lithium borohydride in the product while avoiding product agglomeration caused by excessive concentration, preferably, the molar concentration of the magnesium metal alkyl compound in the reactant is 0.01-1.0 mmol / ml.
[0034] Preferably, the mass ratio of the metal hydride raw material to the functionalized carbon material is 1:5 to 60. Preferably, the alkyl metal Li compound is butyl lithium, and the ratio of butyl lithium to the functional carbon material is 7:1, which can effectively improve the kinetic properties of the lithium borohydride hydrogen storage material and ensure a higher hydrogen storage capacity.
[0035] Preferably, the ultrasonic power of step (2) is 100-600W, the single ultrasonic time is 0.5-2.5 hours, the interval is 10-40 minutes, and the cumulative ultrasonic time is 3-12 hours. The setting of the reaction conditions should take into account the type of carbon material, the type of metal alkyl compound and the dispersion degree of the mixture, and select appropriate parameters to ensure uniform mixing of the system while avoiding excessive energy consumption and solvent volatilization.
[0036] Preferably, the temperature of the solvent thermal reaction is 40-200° C., the reaction time is 15 min-24 h, and the hydrogen pressure is 20-120 bar.
[0037] The invention can obtain metal hydride with nanometer particle size by controlling reaction temperature, reaction time and pressure.
[0038] On the other hand, the present invention also provides a method for preparing a multilayer nanostructured metal hydride and a multilayer nanostructured metal hydride prepared therefrom.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] In the present invention, carbon material is used as a carrier, and the first step of assembling a nano metal catalyst is achieved through a hydrogen thermal reduction reaction of a metal ion salt; then the second step of assembling a multilayer metal hydride is achieved through a solvent thermal reaction to prepare a transition metal-catalyzed multilayer nano metal hydride.
[0041] The carbon material added in the present invention can better disperse the nano metal catalyst, avoid its agglomeration and particle growth in the hydrogen thermal reduction reaction, and maintain its catalytic activity.
[0042] The transition metal source, carrier material and metal hydride body used in the present invention are separated from each other, which enriches the selectivity of the carrier material, increases the types of nano transition metals that can be prepared for catalyzing metal hydrides, and also increases the diversity of the matching between the transition metal and the carrier.
[0043] Compared with existing nano-metal catalysis and nano-confinement, the unique structure prepared by the present invention separates the metal hydride from the carbon material. The intermediate transition metal layer can not only limit the particle size of the metal hydride, but also can efficiently exert catalytic activity in a long cycle, always maintaining the nano-size of the metal hydride. At the same time, the system has a high hydrogen storage capacity, and the hydrogen absorption and desorption temperature is greatly reduced compared with nano-lithium borohydride prepared by other technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 XRD patterns of graphene loaded with Ni in different proportions obtained in step (1) of Example 1.
[0045] Figure 2 XRD patterns of multilayer nano-LiBH4 with different Ni ratios obtained in step (3) of Example 1.
[0046] Figure 3 TEM photos of graphene loaded with Ni in different proportions obtained in step (1) of Example 1, Figure 3 a- Figure 3 d are TEM images of Grs-2Ni, Grs-6Ni, Grs-10Ni and Grs-20Ni, respectively.
[0047] Figure 4 The SEM photos of multilayer nano-LiBH4 with different Ni ratios obtained in step (3) of Example 1 are shown in FIG. Figure 4 a- Figure 4 d corresponds to the SEM images of samples LiBH4-Grs-2Ni, LiBH4-Grs-6Ni, LiBH4-Grs-10Ni and LiBH4-Grs-20Ni, respectively.
[0048] Figure 5 HRTEM image of the LiBH4-Grs-10Ni sample prepared in Example 1 and the selected area electron diffraction (SAED) result of its corresponding area.
[0049] Figure 6 2 are XRD patterns of different nano-LiBH4 prepared in Example 1 and Comparative Example 1.
[0050] Figure 7 The SEM images of different nano-LiBH4 prepared in Example 1 and Comparative Example 1; Figure 7 (a) is the sample LiBH4-Grs-10Ni, Figure 7 (b) is the nano-LiBH4 sample without adding carrier.
[0051] Figure 8 This is a comparison chart of the temperature-dependent hydrogen release curves of different nano-LiBH4 prepared in Example 1 and Comparative Example 1.
[0052] Fig. 9 The temperature-dependent hydrogen release curve and temperature-dependent hydrogen absorption curve of the sample LiBH4-Grs-10Ni prepared in Example 1 and the single graphene-supported nano-LiBH4 sample prepared in Comparative Example 2 are compared, wherein: Fig. 9 (a) is a comparison diagram of hydrogen release curves with temperature. Fig. 9 (b) is a comparison diagram of hydrogen absorption curves with temperature.
[0053] Fig.10 This is a comparison chart of TPD-MS curves of LiBH4-Grs-2Ni, LiBH4-Grs-6Ni, LiBH4-Grs-10Ni and LiBH4-Grs-20Ni prepared in Example 1.
[0054] Fig.11 This is a comparison chart of the temperature-dependent hydrogen absorption curves of LiBH4-Grs-2Ni, LiBH4-Grs-6Ni, LiBH4-Grs-10Ni, and LiBH4-Grs-20Ni prepared in Example 1.
[0055] Fig.12 This is the isothermal hydrogen desorption curve of the LiBH4-Grs-10Ni sample prepared in Example 1.
[0056] Fig.13 It is the isothermal hydrogen absorption curve of the LiBH4-Grs-10Ni sample prepared in Example 1, wherein the isothermal hydrogen absorption temperatures corresponding to (a) and (b) are 350°C, 300°C, 325°C and 150°C, respectively.
[0057] Fig.14 TEM image of the LiBH4-Grs-10Co sample prepared in Example 1.
[0058] Fig.15 This is the HRTEM image of the MgH2-Grs-10Ni sample prepared in Example 1. DETAILED DESCRIPTION
[0059] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0060] Example 1
[0061] Preparation of Ni-catalyzed multilayer nano-LiBH4:
[0062] (1) According to the mass ratio of Ni generated (2wt% / 6wt% / 10wt% / 20wt%), 3 / 9 / 15 / 20 mg of Ni(NO3)2·6H2O and single-layer graphene (30 mg) were weighed respectively, placed in 20 mL of anhydrous ethanol solution and ultrasonically stirred for 20 min. After being evenly dispersed, the mixture was heated and stirred at 500 rpm for 8 h until the liquid in the mixture was completely evaporated. The powder was taken out and placed in a mixed atmosphere of 10% H2 and 90% Ar. It was heated to 400°C at a rate of 5°C / min and kept warm for 2 h. After naturally cooling to room temperature, functional graphene with different proportions of Ni loading was obtained. According to the Ni content in the product, it was recorded as Grs-2Ni, Grs-6Ni, Grs-10Ni, and Grs-20Ni, respectively.
[0063] (2) In an inert atmosphere glove box, 30 mg of Ni-supported functional graphene, 1.6 mL of C4H9-Li (2.0 M in hexane, Aladin) and 645 μL of (C2H5)3NBH3 were placed in 50 mL of n-hexane and stirred for 1 h under ultrasonication. After being fully mixed, the mixture was transferred to a ventilated reactor.
[0064] (3) Fill the reactor with 50 bar of high-purity hydrogen, and heat and stir the reactor in an oil bath at 100° C. for 3 h. After the reaction is completed and cooled to room temperature, centrifugation, washing, filtration, and dynamic vacuum drying at 90° C. for 6 h are performed in an inert atmosphere glove box to finally obtain Ni-catalyzed multilayer nano-LiBH4.
[0065] The sample prepared in the above process is: Ni-catalyzed multilayer nano-LiBH4 (LiBH4-Grs-Ni).
[0066] like Figure 1 As shown in the figure, with the increase of Ni(NO3)2·6H2O dosage, the Ni-loaded graphene sample gradually shows the diffraction peak of Ni.
[0067] like Figure 2 As shown in the figure, it can be found that the multilayer nano-LiBH4 with different Ni ratios all have diffraction peaks of LiBH4, indicating that the main phase of the sample is LiBH4. However, the intensity of these characteristic diffraction peaks is weak, which is related to the reduction of the particle size of LiBH4. It can be seen that the addition of Ni-loaded graphene not only does not affect the formation of LiBH4, but also reduces the particle size of lithium borohydride.
[0068] The graphene loaded with different proportions of Ni obtained in Example 1 was observed by transmission electron microscopy. Figure 3 As shown, Figure 3 (a)- Figure 3(d) Grs-2Ni, Grs-6Ni, Grs-10Ni and Grs-20Ni respectively. It can be found from the figure that as the amount of Ni(NO3)2·6H2O increases, the nano-Ni particles loaded on the graphene surface in the obtained samples gradually increase and the size does not change much. The loading amount of Grs-10Ni reaches the maximum, and the particle size is 2-5nm. When Ni(NO3)2·6H2O continues to increase, the particle size of nano-metal Ni increases significantly.
[0069] Figure 4 SEM photos of multilayer nano-LiBH4 with different Ni ratios. Figure 4 (a)- Figure 4 (d) Corresponding to samples LiBH4-Grs-2Ni, LiBH4-Grs-6Ni, LiBH4-Grs-10Ni and LiBH4-Grs-20Ni. It can be seen from the figure that when LiBH4 accounts for 70wt%, graphene accounts for 27wt%, and nano-Ni metal catalyst accounts for 3wt%, all LiBH4 is fully loaded on the graphene surface, and the nanoparticles do not show obvious agglomeration, and the particle size is 50-70nm.
[0070] Figure 5 The HRTEM photo of the LiBH4-Grs-10Ni sample obtained in Example 1 and the selected area electron diffraction (SAED) results of the corresponding area thereof. The sample consists of a sheet-like carrier, black nanoparticles and gray large nanoparticles. Region 1 with large nanoparticles shows diffraction rings corresponding to the (020) crystal plane of LiBH4, the (311) crystal plane of Ni and the (1(-1)00) crystal plane of graphene. The SAED image of region 2 where only nanoparticles exist only shows the interplanar spacing between the (311) crystal plane of Ni and the (1(-1)00) crystal plane of graphene, indicating that the LiBH4 nanoparticles of the sample are grown on the surface of the Ni nanoparticle layer.
[0071] From the above analysis, it can be seen that Ni-catalyzed multilayer nano-LiBH4 can be successfully prepared using this method, and the addition of functional graphene can significantly reduce the particle size of lithium borohydride.
[0072] Comparative Example 1
[0073] Nano-LiBH4 prepared without adding a carrier is used as a comparative example. The specific preparation process is as follows: In an inert atmosphere glove box, 1.6mL C4H9-Li (2.0M in hexane, Aladin) and 645μL (C2H5) 3NBH3 are placed in 50mL n-hexane and ultrasonically stirred for 1h. After being fully mixed, it is transferred to a ventilated reactor. 50bar high-purity hydrogen is filled into the reactor, and the reactor is heated and stirred in an oil bath at 100°C for 3h. After the reaction is completed and cooled to room temperature, it is centrifuged, washed, filtered and dynamically vacuum dried at 90°C for 6h in an inert atmosphere glove box to finally obtain nano-LiBH4 without adding a carrier.
[0074] Figure 6 The XRD patterns of different nano-LiBH4 prepared in Example 1 and Comparative Example 1. It can be seen that the XRD diffraction peak position of the Ni-catalyzed multilayer nano-LiBH4 is consistent with that of the LiBH4 without a carrier, but the relative intensity of the diffraction peak corresponding to the LiBH4 (200) crystal plane of the multilayer sample is significantly lower than that of the sample without a carrier, which indicates that the orientation of the two is different.
[0075] Figure 7 The SEM images of different nano-LiBH4 prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 7 of Figure 7 (a) and Figure 7 (b) It can be seen that the multilayer nanostructured LiBH4 exists in the form of nanoparticles, which is significantly smaller than the nanorod-shaped LiBH4 (diameter: 500-800nm) without adding a carrier. This shows that the present invention can successfully prepare LiBH4, change its growth mode, and limit its agglomeration and growth.
[0076] Comparative Example 2
[0077] Taking graphene-supported nano-LiBH4 without a nano-Ni catalyst layer as a comparative example, the preparation process is as follows:
[0078] (1) Weigh a few-layer graphene (30 mg) and place it in 20 mL of anhydrous ethanol solution with ultrasonic stirring for 20 min. After it is evenly dispersed, continue heating and stirring at 500 rpm for 8 h until the liquid in the mixture is completely evaporated. Take out the powder and place it in a mixed atmosphere of 10% H2 and 90% Ar. Heat it to 400°C at a rate of 5°C / min and keep it warm for 2 h. After naturally cooling to room temperature, graphene without nickel loading is obtained, which is recorded as Grs.
[0079] (2) In an inert atmosphere glove box, 30 mg of Ni-free graphene, 1.6 mL of C4H9-Li (2.0 M in hexane, Aladin) and 645 μL of (C2H5)3NBH3 were placed in 50 mL of n-hexane and stirred for 1 h under ultrasonication. After being fully mixed, the mixture was transferred to a ventilated reactor.
[0080] (3) Fill the reactor with 50 bar of high-purity hydrogen, and heat and stir the reactor in an oil bath at 100° C. for 3 h. After the reaction is completed and cooled to room temperature, centrifugation, washing, filtration, and dynamic vacuum drying at 90° C. for 6 h are performed in an inert atmosphere glove box to finally obtain single graphene-supported nano-LiBH4.
[0081] The hydrogen release and hydrogen absorption properties of the sample were tested in a vacuum state (the initial vacuum degree was 1×10 -3 Torr) at a heating rate of 2°C / min to 500°C and at a heating rate of 1°C / min to 350°C under 100 bar H2 pressure and kept at this temperature for 6 h. Fig. 9 The temperature-dependent hydrogen release curve and temperature-dependent hydrogen absorption curve of the LiBH4-Grs-10Ni sample prepared in Example 1 and the single graphene-supported nano-LiBH4 prepared in Comparative Example 2 are compared. As can be seen from the figure, Fig. 9 (a) and Fig. 9 (b) shows that the initial dehydrogenation temperature of the LiBH4-Grs-10Ni sample prepared in Example 1 is 100°C, and the first step dehydrogenation peak temperature is 330°C. The initial dehydrogenation temperature (230°C) of the single graphene-loaded nano-LiBH4 sample prepared in Comparative Example 2 is reduced by 130°C, which indicates that the nano-Ni catalytic layer has a higher catalytic activity. When heated to 368°C, the dehydrogenation amount of the LiBH4-Grs-10Ni sample prepared in Example 1 is 7.4wt%, indicating that this multilayer metal hydride has a higher hydrogen storage capacity. The initial hydrogen absorption temperature of the LiBH4-Grs-10Ni sample prepared in Example 1 is 70°C, which is 120°C lower than the initial hydrogen absorption temperature (190°C) of the single graphene-loaded nano-LiBH4 sample prepared in Comparative Example 2. This shows that the Ni-catalyzed multilayer nano-LiBH4 prepared by the method of the embodiment significantly reduces the hydrogen absorption temperature due to the unique nano-catalytic layer.
[0082] Performance Analysis:
[0083] The hydrogen release and hydrogen absorption performances of the LiBH4-Grs-10Ni sample prepared in Example 1 were tested using the temperature-dependent hydrogen release and temperature-dependent hydrogen absorption modes. The test conditions were vacuum (initial vacuum degree was 1×10 -3Torr) was heated to 500°C at a heating rate of 2°C / min and heated to 350°C at a heating rate of 1°C / min under 100 bar H2 pressure and kept at this temperature for 6 h. Figure 8 and Fig. 9 .
[0084] The hydrogen release performance of the nano-LiBH4 sample without carrier prepared in Comparative Example 1 was tested by temperature-dependent hydrogen release mode. The test conditions were vacuum (initial vacuum degree was 1×10 -3 Torr) was heated from room temperature to 500°C at a heating rate of 2°C / min. Figure 8 The figure is a comparison of the hydrogen desorption curves of the LiBH4-Grs-10Ni sample prepared in Example 1 and the nano-LiBH4 sample without a carrier prepared in Comparative Example 1. As can be seen from the figure, the initial hydrogen desorption temperature of the LiBH4-Grs-10Ni sample prepared in Example 1 is 100°C, and the peak temperature of the first step hydrogen desorption is 330°C, which is 103°C lower than the peak temperature (433°C) of the nano-LiBH4 sample without a carrier in Comparative Example 1, which indicates that the nano-confinement synergistic nano-catalysis significantly improves the hydrogen desorption performance of LiBH4.
[0085] The dehydrogenation performance of LiBH4-Grs-2Ni, LiBH4-Grs-6Ni and LiBH4-Grs-20Ni samples prepared in Example 1 was tested by MS-TPD under vacuum (initial vacuum degree was 1×10 -3 Torr) was heated to 550°C at a heating rate of 2°C / min. Fig.10 This is a TPD-MS curve comparison diagram of LiBH4-Grs-10Ni, LiBH4-Grs-2Ni, LiBH4-Grs-6Ni, and LiBH4-Grs-20Ni samples in Example 1. It can be seen from the figure that when the proportion of Ni in the sample increases, the peak temperature of hydrogen desorption of the sample decreases from 360°C to 330°C, and the peak temperature of hydrogen desorption of the LiBH4-Grs-20Ni sample basically does not change, indicating that the hydrogen desorption performance of the LiBH4-Grs-10Ni sample is the best.
[0086] The hydrogen absorption performance of LiBH4-Grs-2Ni, LiBH4-Grs-6Ni and LiBH4-Grs-20Ni samples prepared in Example 1 was tested using the temperature-dependent hydrogen absorption mode. The test conditions were heating to 350°C at a heating rate of 1°C / min under a H2 pressure of 100 bar and keeping the temperature for 6 hours. Fig.11The temperature-dependent hydrogen absorption curves of the LiBH4-Grs-10Ni, LiBH4-Grs-2Ni, LiBH4-Grs-6Ni and LiBH4-Grs-20Ni samples of Example 1 are compared. As can be seen from the figure, when the proportion of Ni in the sample increases, the initial hydrogen absorption temperature of the sample decreases from 270°C to 70°C, and the reversible hydrogen storage capacity increases from 1.6wt% to 7.6wt%. The initial hydrogen absorption temperature of the sample LiBH4-Grs-20Ni shifts to high temperature, and the reversible hydrogen storage capacity decreases to 4.2wt%, indicating that the hydrogen absorption performance of the LiBH4-Grs-10Ni sample is most significantly improved.
[0087] The isothermal dehydrogenation mode was used to characterize the dehydrogenation kinetics of the LiBH4-Grs-10Ni sample prepared in Example 1: under vacuum conditions (initial vacuum degree was 1×10 -3 Torr), heated to 300°C, 325°C and 350°C at a heating rate of 10°C / min and kept at this temperature for a certain time.
[0088] Fig.12 This is the isothermal hydrogen decomposition curve of the LiBH4-Grs-10Ni sample prepared in Example 1. It can be seen from the figure that the sample completely releases 8.23wt% of hydrogen within 50min at 350℃ and releases 6.5wt% of hydrogen within 100min at 300℃, indicating that the multilayer structure of nano-Ni catalysis significantly improves the hydrogen decomposition kinetics of LiBH4.
[0089] The isothermal hydrogen absorption mode was used to characterize the hydrogen absorption kinetics of the LiBH4-Grs-10Ni sample: the initial hydrogen pressure was 100 bar, and the sample was heated to 350°C, 300°C, 325°C and 150°C at a heating rate of 10°C / min and kept for a certain period of time. The results are shown in Figure 2. Fig.13 As shown in (a) and (b).
[0090] like Fig.13 As shown in (a) and (b), the hydrogen desorption product of the sample was completely hydrogenated (8.2wt%) within 300min at 350℃, and 7.8wt% and 7.4wt% of hydrogen were absorbed at 325℃ and 300℃ for 400min and 500min, respectively. Even at 150℃, LiBH4-Grs-10Ni can achieve complete hydrogenation, indicating that the multilayer structure of nano-Ni catalysis significantly improves the hydrogen absorption kinetics of LiBH4.
[0091] Example 2
[0092] Preparation of Co-catalyzed multilayer nano-LiBH4:
[0093] (1) According to the mass ratio of generated Co (10 wt%), 2.96 mg of Co(NO3)2·6H2O and single-layer graphene (30 mg) were weighed and placed in 20 mL of anhydrous ethanol solution with ultrasonic stirring for 20 min. After the mixture was evenly dispersed, it was heated and stirred at 500 rpm for 8 h until the liquid in the mixture was completely evaporated. The powder was taken out and placed in a mixed atmosphere of 10% H2 and 90% Ar. It was heated to 400°C at a rate of 5°C / min and kept warm for 2 h. After naturally cooling to room temperature, functional graphene with a Ni loading of 10 wt% was obtained, which was recorded as Grs-10Co.
[0094] (2) In an inert atmosphere glove box, 30 mg of Grs-10Co, 1.6 mL of C4H9-Li (2.7 M in hexane, Aladin) and 645 μL of (C2H5)3NBH3 were placed in 50 mL of n-hexane and stirred for 1 h under ultrasonication. After being fully mixed, the mixture was transferred to a ventilated reactor.
[0095] (3) Fill the reactor with 50 bar of high-purity hydrogen, and heat and stir the reactor in an oil bath at 100° C. for 3 h. After the reaction is completed and cooled to room temperature, centrifugation, washing, filtration, and dynamic vacuum drying at 90° C. for 6 h are performed in an inert atmosphere glove box to finally obtain Co-catalyzed multilayer nano-LiBH4.
[0096] The sample prepared in the above process is: Co-catalyzed multilayer nano-LiBH4 (LiBH4-Grs-10Co).
[0097] Fig.14 This is a TEM photo of the sample prepared in this embodiment. It can be seen from the figure that graphene carries a large number of dispersed Co nanoparticles and larger LiBH4 nanoparticles.
[0098] Example 3
[0099] Preparation of Ni-catalyzed multilayer nano-MgH2:
[0100] (1) According to the mass ratio of Ni generated (10 wt%), appropriate amounts of Ni(NO3)2·6H2O and few-layer graphene (30 mg) were weighed respectively, placed in 20 mL of anhydrous ethanol solution and ultrasonically stirred for 20 min. After being evenly dispersed, the mixture was heated and stirred at 500 rpm for 8 h until the liquid in the mixture was completely evaporated. The powder was taken out and placed in a mixed atmosphere of 10% H2 and 90% Ar. The mixture was heated to 400°C at a rate of 5°C / min and kept warm for 2 h. After naturally cooling to room temperature, functional graphene with a Ni loading of 10 wt% was obtained, which was recorded as Grs-10Ni.
[0101] (2) In an inert atmosphere glove box, 30 mg of Ni-loaded functional graphene and 2.7 mL of MgBu2 (1.0 M in heptane, Aladin) were weighed and placed in 50 mL of n-hexane for ultrasonic stirring for 1 h. After being fully mixed, they were transferred to a ventilated reactor.
[0102] (3) Fill the reactor with 50 bar of high-purity hydrogen, and heat and stir the reactor in an oil bath at 150° C. for 6 h. After the reaction is completed and cooled to room temperature, centrifugation, washing, filtration, and dynamic vacuum drying at 40° C. for 4 h are performed in an inert atmosphere glove box to finally obtain Ni-catalyzed multilayer nano-MgH2.
[0103] The sample prepared in the above process is: Ni-catalyzed multilayer nano-MgH2 (MgH2-Grs-10Ni).
[0104] Fig.15 This is a HRTEM photograph of the sample prepared in this embodiment. It can be seen from the figure that graphene carries a large number of dispersed Ni nanoparticles and larger MgH2 nanoparticles.
[0105] Embodiments 4 to 9
[0106] The preparation process is substantially the same as that of Example 1, except that the transition metal ion salts used are nickelocene, cobaltocene, titanocene, cobalt nitrate, iron nitrate, manganese nitrate, chromium nitrate, zinc nitrate, copper nitrate, zirconium nitrate, tungsten nitrate, ruthenium nitrate, rhodium nitrate, hafnium nitrate, palladium nitrate, iridium nitrate, platinum nitrate, scandium nitrate, yttrium nitrate, lanthanum nitrate, cerium nitrate, praseodymium nitrate, titanium tetrachloride, titanium trichloride, zirconium tetrachloride, vanadium trichloride, niobium pentachloride, chromium trichloride, pentachloride, Molybdenum chloride, manganese dichloride, iron trichloride, iron dichloride, cobalt dichloride, nickel dichloride, copper dichloride, ruthenium trichloride, rhodium trichloride, palladium dichloride, silver chloride, hafnium tetrachloride, tungsten hexachloride, iridium trichloride, platinum tetrachloride, gold trichloride, scandium trichloride, yttrium trichloride, lanthanum trichloride, cerium trichloride, praseodymium trichloride, the metal alkyl compound used is n-dibutyl magnesium, bismuth magnesium, and the carbon material is carbon nanotubes, carbon fibers, porous carbon, and C3N4. Table 1 lists the basic preparation parameters of different transition metal ion salts as raw materials for synthesizing transition metal catalyzed multilayer nanometal hydrides.
[0107] Table 1 Synthesis parameters of multilayer nanometal hydrides catalyzed by different transition metals
[0108]
Claims
1. A method for preparing a multilayer nanostructured metal hydride, characterized in that: include: (1) adding a transition metal ion salt and a carbon material to a polar solvent, mixing, heating and stirring to obtain a solid powder, and subjecting the solid powder to a hydrogen thermal reduction reaction to obtain a functionalized carbon material; (2) adding a metal hydride raw material and a functionalized carbon material into an organic solvent, ultrasonically treating and mixing to obtain a mixed solution, wherein the metal hydride raw material is a mixture of an alkyl metal Mg compound or an alkyl metal Li compound and a borane compound; (3) Under a hydrogen atmosphere, the mixed solution of step (2) is subjected to a solvothermal reaction, and then centrifuged, washed, filtered, and dried to obtain a multilayer nanostructured metal hydride.
2. The method for preparing a multilayer nanostructured metal hydride according to claim 1, characterized in that: The mass ratio of the transition metal ion salt to the carbon material is 0.01-100.
3. The method for preparing the multilayer nanostructured metal hydride according to claim 2, characterized in that: The mass ratio of the transition metal ion salt to the carbon material is 0.1-10.
4. The method for preparing a multilayer nanostructured metal hydride according to claim 1, characterized in that: The transition metal ion salt includes one or more of transition metallocenes, transition metal nitrates, and transition metal chlorides; The transition metallocene is one or more of nickelocene, cobaltocene, and titanocene; The transition metal nitrate is one of nickel nitrate, cobalt nitrate, iron nitrate, manganese nitrate, chromium nitrate, zinc nitrate, copper nitrate, zirconium nitrate, tungsten nitrate, ruthenium nitrate, rhodium nitrate, hafnium nitrate, palladium nitrate, iridium nitrate, platinum nitrate, scandium nitrate, yttrium nitrate, lanthanum nitrate, cerium nitrate, and praseodymium nitrate; The transition metal acetate is one of nickel acetate, cobalt acetate and iron acetate; The transition metal chloride is one of titanium tetrachloride, titanium trichloride, zirconium tetrachloride, vanadium trichloride, niobium pentachloride, chromium trichloride, molybdenum pentachloride, manganese dichloride, ferric chloride, ferric dichloride, cobalt dichloride, nickel dichloride, copper dichloride, ruthenium trichloride, rhodium trichloride, palladium dichloride, silver chloride, hafnium tetrachloride, tungsten hexachloride, iridium trichloride, platinum tetrachloride, gold trichloride, scandium trichloride, yttrium trichloride, lanthanum trichloride, cerium trichloride, and praseodymium trichloride.
5. The method for preparing the multilayer nanostructured metal hydride according to claim 4, characterized in that: The transition metal ion salt is a transition metal nitrate.
6. The method for preparing multilayer nanostructured metal hydride according to claim 1, characterized in that: The carbon material is one or more of graphene, carbon nanotubes, carbon fibers, porous carbon, carbon nitride, graphene doped with nitrogen, boron or phosphorus atoms, carbon nanotubes, carbon fibers, and porous carbon.
7. The method for preparing multilayer nanostructured metal hydride according to claim 1, characterized in that: The polar solvent is water and / or ethanol.
8. The method for preparing multilayer nanostructured metal hydride according to claim 1, characterized in that: The heating and stirring temperature is 60-90° C., the stirring speed is 300-1000 rpm, and the stirring time is 3-12 h.
9. The method for preparing multilayer nanostructured metal hydride according to claim 1, characterized in that: The alkyl metal Li compound is n-butyl lithium, and the alkyl metal Mg compound is di-n-butyl magnesium and / or bis(cyclopentadienyl) magnesium.
10. A multilayer nanostructured metal hydride, characterized in that: The multilayer nanostructured metal hydride is prepared by the method for preparing a multilayer nanostructured metal hydride according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-capacity composite hydrogen storage material and hydrogen discharge method
CN102442646A
Highly reactive metal hydrides, process for their preparation and use
CN107995905A
Nano lithium borohydride as well as in-situ preparation method and application thereof
CN112320757A
MOF-derived carbon confinement magnesium-based nano hydrogen storage material and preparation method thereof
CN116618671A
Reversibly storing hydrogen system and its using methods
CN1938220A
Cited By
Preparation method and application of dual-phase nanorod catalyst
CN120861076A
Preparation method and application of a two-phase nanorod catalyst
CN120861076B